Gemcitabine Plus Nab-Paclitaxel Versus FOLFIRINOX in Locally Advanced, Unresectable Pancreatic Cancer: A Multicenter Observational Study (NAPOLEON Study). Issue 7 (4th August 2021) - Arima, Shiho; Kawahira, Machiko; Shimokawa, Mototsugu; Ido, Akio; Koga, Futa; Ueda, Yujiro; Nakazawa, Junichi; Komori, Azusa; Otsu, Satoshi; Fukahori, Masaru; Makiyama, Akitaka; Taguchi, Hiroki; et al.
Abstract : Objectives: FOLFIRINOX (FFX, a combination of oxaliplatin, irinotecan, fluorouracil, and leucovorin) and gemcitabine plus nab-paclitaxel (GnP) have been used as standard, first-line treatments for advanced pancreatic cancer. However, no study has compared the efficacy of the 2 regimens. This study retrospectively compared the efficacy and safety of the 2 regimens in patients with locally advanced pancreatic cancer. Methods: We reviewed the records of patients with locally advanced pancreatic cancer who started FFX or GnP as first-line chemotherapy as part of a multicenter retrospective study in patients with unresectable pancreatic cancer treated with FFX or GnP (NAPOLEON study). Results: Sixteen of the 63 patients were treated with FFX, and the other 47 patients were treated with GnP between December 2013 and March 2017. There were no significant differences in median overall survival rate between the GnP (15.5 months) and FFX (14.3 months, P = 0.60) groups or median progression-free survival rate between the GnP (8.8 months) and FFX (8.1 months, P = 0.51) groups. Both treatments were generally well tolerated, although anorexia was more severe in the FFX group than in the GnP group. Conclusions: The effects of FFX and GnP were similar but resulted in different toxicities, which could guide agent choice.